The Opening of Pandora's Box: An Emerging Role of Long Noncoding RNA in Viral Infections - Wang, Pin (Frontiers in Immunology, 2019)
Emerging evidence has proved that long noncoding RNAs (lncRNAs) participate in various physiological and pathological processes. Recent evidence has demonstrated that lncRNAs are crucial regulators of virus infections and antiviral immune responses. Upon viral infections, significant changes take place at the transcriptional level and the majority of the expression modifications occur in lncRNAs from both the host and viral genomes with dynamic regulatory courses. These lncRNAs exert diverse effects. Some are antiviral either through directly inhibiting viral infections or through stimulating antiviral immune responses, while others are pro-viral through directly promoting virus replication or through influencing cellular status, such as suppressing antiviral mechanisms. Consequently, these dynamic regulations lead to disparate pathophysiological outcomes and clinical manifestations. This review will focus on the roles of lncRNAs in viral infection and antiviral responses, summarize expression patterns of both host- and virally derived lncRNAs, describe their acting stages and modes of action, discuss challenges and novel concepts, and propose solutions and perspectives. Research into lncRNA will help identify novel viral infection-related regulators and design preventative and therapeutic strategies against virus-related diseases and immune disorders.